(untitled) (Global Journal of Management and Business Research, 2021)
In this paper we would be getting to know the basics of Ecommerce and how it has benefited us from past several decades and how its continuing to benefit us along with its various practical implementations, how it is shaping our economy, how it helps in career opportunities and how it is becoming a new trend. As it has its share of positive results, there are some negative outcomes which we will be getting to know and how it can be resolved.